The Role of the Tourism Office in Improving the Community's Economy at the Tourism Object in Pasaman Regency - Neti Hairani; Beni Putra Hanafi (IAIN Batusangkar, 2022)
The main problem in this study is the lack of awareness on the management of the rimbo orphanage nature reserve tourism, so that it has an impact on the economic income of the community which is getting less and less to anticipate this problem, the important role of the local government. The purpose of this study is to find out the potential that exists in tourist objects, to find out the empowerment carried out in reviving tourism objects, and to find out the empowerment carried out by the community in promoting the Rimbo Panti Nature Reserve Tourism Object in Kecamatan Panti , Kabupaten Pasaman. The type of research used is field research with qualitative methods and descriptive approaches. Data collection techniques are observation, interviews, and documentation. The data analysis technique used by the researcher is data reduction, data presentation and conclusion drawing. The guarantor of the validity of the data in this study uses source triangulation, technique triangulation and time triangulation. Based on the research conducted, it was found that the potential that exists in the Rimbo Panti Nature Reserve Tourism Object is hot springs, hot baths and the latest specific drink, namely Roasted Coffee. Empowerment was carried out to revive Rimbo Panti through improving infrastructure and also maintaining the beauty of the flora and fauna of the Rimbo Panti Nature Reserve Tourism Object, but this has not been carried out properly due to Covid-19 so that the empowerment program has not been implemented optimally. Meanwhile, the empowerment carried out by the community to promote the Rimbo Panti Nature Reserve Tourism Object through social media, electronic media and has also been broadcast on TVRI Padang.